2019
DOI: 10.1021/acsomega.9b02403
|View full text |Cite
|
Sign up to set email alerts
|

Effective Antibacterial Glass Fiber Membrane Prepared by Plasma-Enhanced Chemical Grafting

Abstract: This paper reports a novel glass fiber membrane with an effective antibacterial performance by chemical grafting of quaternary ammonium salt (QAS) which is enhanced by a plasma bombardment technique. Plasma bombardment as a pretreatment of the membrane can increase the QAS anchored on the membrane from 0.8 to 1.3 wt %. The chemical grafting technique can increase the membrane zeta potential from negative values to positive values in aqueous solutions at various pHs. Furthermore, the plasma-enhanced chemical-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…As early as 1916, Jacobs et al found that most of the QAS obtained by the reaction of hexamethylenetetramine with various substituted benzyl or alkyl halides had strong bactericidal activity [75]. Guo et al [76] pre-treated glass fibre membranes with plasma bombardment and further used chemical grafting to anchor QAS molecules on the surface of glass fibre membranes and found that the antibacterial effect on the surface of glass fibre membranes was significant after modification by QAS [77][78]. Wan et al [79] synthesised QAS copolymers, which exhibited excellent antibacterial properties due to their better water solubility and easier access to bacteria.…”
Section: Contact Bactericidal/bacteriostatic Paintmentioning
confidence: 99%
“…As early as 1916, Jacobs et al found that most of the QAS obtained by the reaction of hexamethylenetetramine with various substituted benzyl or alkyl halides had strong bactericidal activity [75]. Guo et al [76] pre-treated glass fibre membranes with plasma bombardment and further used chemical grafting to anchor QAS molecules on the surface of glass fibre membranes and found that the antibacterial effect on the surface of glass fibre membranes was significant after modification by QAS [77][78]. Wan et al [79] synthesised QAS copolymers, which exhibited excellent antibacterial properties due to their better water solubility and easier access to bacteria.…”
Section: Contact Bactericidal/bacteriostatic Paintmentioning
confidence: 99%
“…Xia's group reported the formation of an antibacterial glass fiber membrane by plasma-enhanced chemical grafting (PCG) of 3-(trimethoxysilyl)propyldimethyloctadecyl ammonium chloride. 235 The plasma bombardment of fiberglass has proven to be an effective glass pretreatment method. Compared with other surface activation methods (for example, activation by acid and alkaline or ozone surface activation), plasmaenhanced surface functionalization is more environmentally friendly and easier to operate.…”
Section: ■ Qac-embedded Coatings As a Promising Strategy For Biofilm ...mentioning
confidence: 99%
“…If there are no necessary functional groups on the surface, it can be activated by plasma technology. Xia’s group reported the formation of an antibacterial glass fiber membrane by plasma-enhanced chemical grafting (PCG) of 3-(trimethoxysilyl)­propyldimethyloctadecyl ammonium chloride . The plasma bombardment of fiberglass has proven to be an effective glass pretreatment method.…”
Section: Qac-embedded Coatings As a Promising Strategy For Biofilm Co...mentioning
confidence: 99%
“…[ 91 ] Whereas the nonpolar chains of QAS/PS interact with the nonpolar, inner part of cytoplasmic membranes, the positive charges on the groups interact with the polar outer part of the membranes, disrupting the electrical and osmotic balance and other important functions of the cell to culminate in bacteriolysis. [ 92 ] QASs have been plasma‐grafted on different surfaces, namely polypropylene, [ 93 ] glass fiber membranes, [ 94 ] and polyethylene foils [ 95 ] to impart antibiofouling properties.…”
Section: Antibiofouling Self‐decontaminating and Biomimetic Surfacesmentioning
confidence: 99%